Faktor-Faktor yang Mempengaruhi Keputusan Konsumen dalam Memilih Rumah Sewa Harian di Kota Pontianak - Sugito Sudjalmo (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
The purpose of this paper is to analyzed the factors that influence the consumer decisions in choosing daily rental houses (homestay) in Pontianak. The factors studied included price, location, facilities, cleanliness, security, online reviews, and online promotions as independent variables, while the rental decision served as the dependent variable. The research method used was quantitative descriptive analysis using a Likert-scale questionnaire (1–5). The study respondents were visitors who had rented homestays, so the dependent variable was definite. Data were collected through questionnaires distributed to 100 respondents and analyzed using descriptive techniques in the form of frequency distributions, percentages, and averages. The results showed that cleanliness received the highest average score (4.60), followed by facilities (4.50), and security (4.42), making these three factors the dominant factors influencing rental decisions. Location (4.32), price (4.30), digital promotions (4,18) and online reviews (4.10) also had a significant influence, just slightly below the above three dominan factors. The conclusion of this study confirms that cleanliness, facilities, and security are key factors that homestay managers must consider to increase customer appeal and satisfaction. The recommendations given are for homestay managers to maintain cleanliness, strengthen security systems, provide relevant amenities, and utilize online promotions and reviews effectively.